2014
DOI: 10.3390/d6020296
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Phytoplankton Assemblages in Two Coastal Ecosystems in Relation to Environmental Factors (Corsica, NW Mediterranean Sea)

Abstract: Corsica Island is a sub-basin of the Northwestern Mediterranean Sea, with hydrological features typical of both oligotrophic systems and eutrophic coastal zones. Phytoplankton assemblages in two coastal ecosystems of Corsica (the deep Bay of Calvi and the shallow littoral of Bastia) show contrasting patterns over a one-year cycle. In order to determine what drives these variations, seasonal changes in littoral phytoplankton are considered together with environmental parameters. Our methodology combined a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
1
13
0
3
Order By: Relevance
“…Furthermore, there is a permanent background DMSP stock of 600 mol m −2 corresponding to winter time DMSP leaf content (2 mol g dw −1 ) and leaf biomass (300 g dw m −2 ), that is still 60 higher than the maximum yearly stock related to phytoplankton. The yearly maximum DMSP content of phytoplankton we estimated is anyway most probably largely over-estimated since the dominant diatoms during the spring phytoplankton bloom reported in the Bay of Revellata by Garrido et al (2014) have DMSP:Chl-a ratios much lower than the average value used above such as Chaetoceros didynus and Chaetoceros socialis or even DMSP cellular quota that are below detection limit such as Chaetoceros decipiens and Chaetoceros simplex (Keller et al, 1989).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, there is a permanent background DMSP stock of 600 mol m −2 corresponding to winter time DMSP leaf content (2 mol g dw −1 ) and leaf biomass (300 g dw m −2 ), that is still 60 higher than the maximum yearly stock related to phytoplankton. The yearly maximum DMSP content of phytoplankton we estimated is anyway most probably largely over-estimated since the dominant diatoms during the spring phytoplankton bloom reported in the Bay of Revellata by Garrido et al (2014) have DMSP:Chl-a ratios much lower than the average value used above such as Chaetoceros didynus and Chaetoceros socialis or even DMSP cellular quota that are below detection limit such as Chaetoceros decipiens and Chaetoceros simplex (Keller et al, 1989).…”
Section: Discussionmentioning
confidence: 70%
“…Within, the P. oceanica canopy, phytoplankton material was found to be mostly detrital, and living cells corresponded to cyanobacteria that are characterized by low DMSP content (Table 1). Further, in August, when DMSPd measurements were carried out, Chl-a in surface waters were extremely low, typically <0.2 g L −1 (own data not shown; Garrido et al, 2014). Hence, it is possible that DMSPd could accumulate more within the canopy than what is typically observed in the planktonic community of surface waters.…”
Section: Discussionmentioning
confidence: 95%
“…The phytoplanktons whose original habitat was offshore came from fishing boats and were carried by ballast water or stucked to the hull. Garrido et al (2014) also found that many non-littoral species were also found at the enclosed mariculture area at Corsica, in the Mediterranean Sea.…”
Section: The Correlations Between the Environmental Characteristics Wmentioning
confidence: 77%
“…and Melosira sp. This group dominated the seashore area, particularly the areas which had mariculture activities in them (Garrido et al, 2014;George & Atakpa, 2015;Akter et al, 2015). The group which had a low abundance consisted of 12 species.…”
Section: The Correlations Between the Environmental Characteristics Wmentioning
confidence: 99%
“…First, phytoplanktonic communities in Corsica are dominated by nano-and picophytoplankton, just as in all oligotrophic zones (Garrido et al, 2014). Heimbürger et al (2010) showed that Hg methylation is enhanced in the presence of nano-and picophytoplankton.…”
Section: Geographical Comparison Of Hg Concentration In Red Mulletmentioning
confidence: 98%